How to fight anti-Semitism - Weiss, Bari (Crown, 2019)
"No longer the exclusive province of the far right and far left, anti-semitism finds a home in identity politics and the reaction against identity politics, in the renewal of "America first" isolationism and the rise of one-world socialism. An ancient hatred increasingly allowed into modern political discussion, anti-semitism has been migrating toward the mainstream in dangerous ways, amplified by social media and a culture of conspiracy that threatens us all. This timely book is Weiss's cri de couer: an unnerving reminder that Jews must never lose their hard-won instinct for danger, and a powerful case for renewing Jewish and liberal values to guide us through this uncertain moment. Not just for the sake of America's Jews, but for the sake of America"--